Preliminary Product Acceptance and Initial Price of Virgin Red Palm Oil on African Expatriate Communnity in Jakarta - Mokhamad Syaefudin Andrianto (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2019)
The development of the palm oil downstream industries is still limited eventhough various products can be made. The market acceptance becomes one of the important considerations. The research objective was to analyze the acceptance and initial price a new product of Virgin Red Palm Oil (VRPO), a kind of Red Palm Oil (RPO), one of the potential downstream palm oil products. A survey was conducted in Jakarta with African expatriate community as respondents. The samples of product VRPO with the brand of “Salmira” were given. After they tasted, they filled the questionnaire. The acceptance perception product was measured by likert scale, and initial price with the willingness to pay methods was investigated by open ended questions. The results analysed by average aprroached and optimum price used linear and logarithmic regression. This study found that product perception was very good especially in familliarity and reccomendation to buy. The new product was similar to the product available in their origin countries and when the product available, almost 90 % respondents would like to buy the product. Other results showed that packaging was preferred in 1 000 ml. The maximum willingnes to pay for 1 liter was IDR 150 000, and the minimum was IDR 20 000. The average price was IDR 70 370, and the optimum price with linear regression approached was IDR 70.809 and with the logarithmic regression approached was IDR 62.628. This study provides empirical evidence that the product is prospective eventhough it is still in the limited scope.The range willingness to pay also supports the decision maker to give the initial price.